Analisis Struktur dan Nilai Kehidupan Yang Terdapat Pada Novel TERUSIR Karya Hamka - Lilis Rosmiati; Iis Ristiani (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to: (1) Describe the intrinsic elements in Hamka's novel Exile. (2) Describe the values of life in Hamka's novel Exile. This research is a descriptive qualitative research. The subject of this study is Hamka's 125-page novel Terusir, published in Jakarta by Gema Insani in 2020. The data collection is carried out by documentation techniques. The results showed; 1) themes of struggle, romance and betrayal; 2) characters and characterizations: Mariah a loyal, loving and patient woman, Azhar is a hardworking but careless man, Haji Abdul Halim is so wise and patient, Sofyan is a loyal, intelligent and wise person, Emi is a good girl, intelligent and loyal, pakcik wife is jealous, Wirja has a vengeful and spiteful nature; 3) The setting is in the house of Mariah's uncle, the house of Mr. and Mrs. Van Oost, the Elephant Building, the Sofyan Office, the prison and the airport. The setting of the events in this novel takes place around the 1900s during the Dutch colonial period. The setting is depressing, romantic and emotional; 4) The plot contained in this novel is a forward plot; 5) The point of view is an all-knowing third-person point of view. In addition to the above elements, the novel Exile has value, namely: teaching about modesty, so that we remain grateful and surrender to the creator and do not slander.